From the Fiqh of Minority to Cosmopolitan Fiqh An Analysis. (1st January 2014) - ,
Abstract : The convergence of Muslims in Europe and America from different Muslim majority societies conjures the idea of a multicultural milieu. The West has indeed become a crossroad of civilizations and cultures and such intersection is explicable for a cosmopolitan fiqh reflective of all the Muslims. The convergence of Muslims of different Madhhabs, cultural and social background in the West does not simply delineates the universality and homogeneous ground, but it also nicely presents the laboratory for the mixture of all Madhhabs that have long divided the Muslims. Bridging the past and the present is the golden aim of cosmopolitan fiqh and presenting Islam as a comprehensive faith reflecting on the entirety of life. Cosmopolitan fiqh can be yet an avenue for Muslims to showcase their worth and extent to which they can contribute in the societies they are part of.